Some Factors Affecting Spermatozoan Motiiity of Two Freshwater Fishes, Puntius filamentosis and Amblypharyngodon mola - C.E., Paul; V., Jayaprakas (Fishery Technology, 2025)
The effect of certain factors influencing the motiiity of spermatozoa of two species of fresh water fishes, Puntius filamentosis and Amblypharyngodon mola was evaluated. The biological properties and quality of semen were examined. The biological properties and quality of spermatozoan motiiity was estimated by activating in fresh water, distilled water, 1% glucose and fertilizing solution. The spermatozoa showed maximum duration of motiiity in fertilizing solution in both fishes. In A. mola the spermatozoan motiiity gradually increased from 1% seawater reaching the longest duration of motiiity of 1611.2 sec at 15% seawater and thereafter declined to 181 sec at 20% seawater. In P. filamentosis maximum duration of spermatozoan motiiity was observed at 5% seawater and then declined showing no motiiity at 20% seawater. The spermatozoa of P. filamentosis exhibited maximum duration of motiiity at lO* and in A. mola at 20oC. Duration of motiiity increased with increase in the pH showing the maximum motiiity at pH 8.0 in both fishes. The spermatozoa of both fishes showed high percentage viability. The sperm cell concentration of P. filamentosis (20.56 x 109 sperms ml"1) was less than that of A. mola (23.71 x 109 sperms ml"1).